2021
DOI: 10.1002/htj.22117
|View full text |Cite
|
Sign up to set email alerts
|

Mass and heat transport impact on the peristaltic flow of a Ree–Eyring liquid through variable properties for hemodynamic flow

Abstract: Variable properties play a prominent role in analyzing the blood flow in narrow arteries. Specifically, considering the variation of thermal conductivity and viscosity helps in the understanding of the rheological behavior of blood and other biological fluids, such as urine, spermatozoa, and eye drops. Inspired by these applications, the current study incorporates the impact of variable thermal conductivity and viscosity for modeling the peristaltic flow of a Ree–Eyring liquid through a uniform compliant chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Numerous investigations have recently been adopted on the effects of hybrid nanofluids and ribs in microchannels [ 30 , 31 , 32 , 33 , 34 , 35 ]. Additional applications of nanofluids in engineering problems were reported in [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have recently been adopted on the effects of hybrid nanofluids and ribs in microchannels [ 30 , 31 , 32 , 33 , 34 , 35 ]. Additional applications of nanofluids in engineering problems were reported in [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sreedevi et al 15 analyzed the influence of Soret and Dufour effects on MHD flow with heat and mass transfer past a permeable stretching sheet in presence of thermal radiation and found that an increase in values of thermal radiation, viscous dissipation, suction/injection coefficient and chemical reaction results in the increase of velocity, temperature, and heat-mass transfer rates. A few new research in this area has been conducted, including the varied impacts reported in References [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the entropy generation is a key aspect of every heat transport development. Other recent surveys about this topic can be found in references (Rashad et al , 2018; Basak and Roy, 2010; Abbas et al , 2021; Mondal et al , 2021; Sahoo and Nandkeolyar, 2021; Mebarek-Oudina, 2019; Abo-Dahab et al , 2021; Marzougui et al , 2021a; Shafiq et al , 2021; Dadheech et al , 2020; Djebali et al , 2021; Warke et al , 2021; Rajashekhar et al , 2021; Swain et al , 2021a; Mebarek‐Oudina, 2017; Mebarek-Oudina et al , 2020b; Mebarek-Oudina et al , 2021b; Marzougui et al , 2021b; Zaim et al , 2020b; Swain et al , 2021b; Mebarek-Oudina et al , 2021c).…”
Section: Introductionmentioning
confidence: 99%